Access to justice - Sandefur, Rebecca, 1966- (Bingley, UK : Emerald JAI, 2009)
Around the world today, access to justice enjoys an energetic and passionate resurgence as an object both of scholarly inquiry and political contest, as both a social movement and a value commitment motivating study and action. This volume brings together cutting-edge work from practitioners and scholars in law, political science, social psychology, sociology, and sociolinguistics. This work reflects a high degree of sophistication in empirical analysis, and, as importantly, evidences a deeper engagement with social theory than past generations of scholarship. Good understanding is valuable both for its own sake and because it is essential to good policy. The richer conceptual frameworks employed by these scholars create more sophisticated research questions that in turn inform a more nuanced policy agenda. This research - on rights knowledge and police procedure, race and jury deliberation, tort reform and access to lawyers, self-interest and public service, ordinary people's experience with everyday troubles - reveals new discoveries about law and social process and provides foundation for a deeper understanding of access to justice that can inform wiser, more effective policies.
Access to justice : classical approaches and new directions -- The legal problems of everyday life / Ab Currie -- Failure to recall : indications from the English and Welsh Civil and Social Justice Survey of the relative severity and incidence of civil justice problems / Pascoe Pleasence, Nigel J. Balmer and Tania Tam -- Rights consciousness in criminal procedure : a theoretical and empirical inquiry / Kathryne M. Young -- Beyond court interpreters : exploring the idea of designated Spanish-speaking courtrooms to address language barriers to justice in the United States / Kwai Hang Ng -- Access to juries : some puzzles regarding race and jury participation / Mary R. Rose -- Legal services for the poor : access, self-interest, and pro bono / Stephen Daniels and Joanne Martin -- Expanding access to lawyers : the role of legal advice centers / Masayuki Murayama -- Personal responsibility v. corporate liability : how personal injury lawyers screen cases in an era of tort reform / Mary Nell Trautner -- When bad things happen : toward a sociology of troubles / Jennifer Earl -- Comment : a revival of access to justice research? / Bryant G. Garth.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Justice, Administration of; Legal aid; Legal assistance to the poor; Civil rights; Sociological jurisprudence; Causes & prevention of crime; Criminal investigation & detection; Social Science -- Criminology